Persoalan Pelestarian Bahasa Ciacia: Refleksi atas Etika Diskursus - Mikka Wildha Nurrochsya (Jurnal Pendidikan dan Kebudayaan, 2015)
Ciacia language is the language used by the Ciacia community in Southeast Sulawesi. In August 2009, the Mayor of Baubau, Southeast Sulawesi, enacted policy to adapt the Korean alphabet (Hangeul) into the Ciacian alphabet because the Ciacia language does not have its own script. This decision immediately caused controversy as some agreed and others disagreed. This paper has two objectives. First, it seeks to observe the diverse opinions surrounding the decision to adapt the Korean alphabet into the Ciacia alphabet. Secondly, the paper offers a reflection on the ethical discourse surrounding the adaptation of the Korean alphabet into the Ciacia alphabet. This study used case studies and took a qualitative approach. Results showed that there was not enough support given to the public to encourage practical discourse and offer a no-pressure environment. Support was neither given within the Ciacia community in Baubau nor outside Baubau to strengthen Ciacia language and culture. This study concluded that those who agree with the adaptation are likely to understand it as serving an instrumental function in furthering economic and political interests. Meanwhile, those who oppose the adaptation are more concerned with culture preservation. Proper discourse has not taken place in regards to this issue. Thus, the debate continues to be unresolved.ABSTRAK Bahasa Ciacia merupakan bahasa yang digunakan oleh masyarakat Ciacia di Sulawesi Tenggara. Walikota Baubau, Sulawesi Tenggara pada Agustus 2009 memutuskan kebijakan mengadaptasi aksara Korea (Hangeul) menjadi aksara Ciacia karena Bahasa Ciacia tidak mempunyai aksara sendiri. Keputusan ini menimbulkan reaksi baik pro maupun kontra. Tulisan ini mempunyai dua tujuan Pertama, ingin mengetahui pendapat-pendapat tentang kasus adaptasi aksara Korea menjadi aksara Ciacia. Kedua, ingin mengetahui implementasi etika diskursus untuk menyelesaikan kasus adaptasi aksara Korea menjadi aksara Ciacia. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Hasil penelitian menunjukan bahwa kasus adaptasi ini kurang memberikan ruang publik untuk diskursus praktis dalam suasana saling pengertian dan bebas dari tekanan, baik dalam masyarakat Ciacia di wilayah Kota Baubau maupun masyarakat Ciacia di luar Kota Baubau sebagai pendukung bahasa dan budaya masyarakat Ciacia. Penelitian ini menyimpulkan bahwa pihak yang pro adaptasi lebih cenderung berorientasi pada rasionalitas instrumental yakni kepentingan ekonomis dan politis, sedangkan pihak yang kontra berorientasi pada pelestarian budaya. Dalam kasus adaptasi ini belum diterapkan etika diskursus secara memadai sehingga tetap menjadi perdebatan yang tak terselesaikan.